(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Markheva O. E. Standardization of vocational training of foreign language teachers in European countries. The article deals with the practice of standardization of the professional training of teachers of foreign languages in higher educational establishments of Germany, Swiss and Austria in the context of the Bologna Process. The theoretical bases of the professional training of teachers of foreign languages and curricula of leading higher educational establishments of these countries are studied.